GENDER APPROACH IN THE BUDGET PROCESS - Tsiupa , O.P.; Kondur , O.S.; Vasyliuk, M.M. (The actual problems of regional economy development, 2022)
The article is aimed at studying the nature and benefits of gender approach in the budget process. After all, today Ukraine is on the path of reforms and transformations, the progress of which is very tangible. One of the important directions is to reform the public financial management system. Reforming the public finance system based on the use of innovative tools is an important component - the foundation of sustainable development of Ukraine. The gender approach is the newest tool that takes into account a wide range of issues, the solution of which creates equal opportunities for all members of society and ensures a fair distribution of taxpayers' funds between women and men and / or their groups. The application of this tool involves the inclusion of gender aspects in budget-funded programs, which will make it possible to see how different measures of budget programs affect people depending on their gender, age, place of residence, and will measure the impact of these measures on reducing gender gaps. The research identified the advantages of applying a gender approach to the budget process, in particular: improving the quality of public services for the population, as it defines clear guidelines for a particular consumer; increasing economic growth and poverty reduction, as well as efficient use of budget funds. The article also proposes ways to ensure the sustainability of this tool in Ukraine: continue work on institutionalizing gender budgeting, spreading the process of applying this tool to all major managers of state and local budgets and increase the availability and quality of data broken down by article. Thus, the Government needs to continue the process of gender mainstreaming in the budget process, which will enable the state to properly perform social functions and ensure sustainable development of Ukraine, as well as accelerate integration processes and promote the implementation of best practices in achieving gender equality in national practice